Class Management as a Strategy to Increase Student Learning Motivation - Wijayanti, Tri; Katni, Katni; Dwi Laksana, Sigit (CV. Edutechnium Indonesia, 2023)
This study is motivated by students' lack of enthusiasm in dealing with learning at school. It is necessary to have several methods or strategies carried out by teachers to motivate students to be more active in learning; therefore, this study was conducted based on describing strategies for classroom management planning, implementation of classroom management, supporting and inhibiting factors in classroom management. Many factors affect student enthusiasm, and motivation is needed to arouse student enthusiasm. The purpose of this study is to find out the classroom management strategies carried out by teachers to students, know the process of implementing classroom management, and find out some of the supporting and inhibiting factors in classroom management that occur Madrasah Ibtidaiyah Negeri (MIN) 7 Ponorogo. This study uses a qualitative approach with case study. The study results on classroom management strategies to increase students' learning motivation at MIN 7 Ponorogo are as follows: (1) Aims to train students' discipline and teach them to have a spirit of caring for the environment and are expected to be able to build student enthusiasm and have a positive impact on madrasas, (2). Educators give a stimulus to students so that students are always enthusiastic when doing the learning. Teachers use media such as LCD projectors or images and other media such as sound to support learning. (3) There are supporting factors in the professional educators and teachers who have close attention to students and classrooms, as well as the proactive role of the surrounding community for madrasas, and the inhibiting factor in the form of a large number of students in one class, as happened in class V at MIN 7 Ponorogo.